(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Background: The integration of digital technologies into healthcare systems has transformed the landscape of healthcare delivery, necessitating a nuanced understanding of the sociotechnical dynamics involved. This study aims to explore and synthesize the literature on sociotechnical aspects of digital health to elucidate key themes, trends, and insights shaping the adoption and implementation of digital health innovations. Aim: The aim of this study is to systematically review and analyze existing literature to identify recurring themes, sub-themes, and trends related to the sociotechnical dimensions of digital health. By synthesizing evidence from a diverse range of studies, this research seeks to provide a comprehensive overview of the factors influencing the adoption, implementation, and impact of digital health technologies. Method: A systematic literature review was conducted using databases such as PubMed, Google Scholar, and Scopus. Keywords related to digital health, sociotechnical systems, healthcare delivery, and adoption factors were employed to identify relevant studies published between 2018 and 2022. A total of 15 studies were selected based on predetermined inclusion criteria, and data extraction involved synthesizing key findings, methodologies, and conclusions from each study. Thematic analysis was employed to identify and analyze recurring themes and sub-themes across the selected literature. Results: The analysis revealed several key themes, including sociotechnical ethics, users’ invisible work, factors influencing adoption, and the impact of electronic health records. Sub-themes such as co-design processes, socio-technical practices in long-term care, and challenges and opportunities for cloud technology were also identified. Trends highlighted the complexity of sociotechnical interactions and the importance of considering diverse perspectives in digital health research. Conclusion: By synthesizing evidence from a diverse range of studies, this research contributes to a deeper understanding of the sociotechnical dimensions of digital health. The findings underscore the importance of considering social, organizational, and technical factors in the design, implementation, and evaluation of digital health interventions. Addressing sociotechnical challenges is crucial for realizing the full potential of digital health technologies in improving healthcare delivery.